Optimum Population in Rural Areas: Empirical Evidence from the Franc Zone - Stryker, J. Dirck (Quarterly Journal of Economics, 1977)
A theoretical analysis of optimum population, 179.—Empirical evidence from the Franc Zone, 183.—Possibilities of bias, 189.—Conclusion, 191.